Activation of Astrocytic μ-opioid Receptor Elicits Fast Glutamate Release Through TREK-1-Containing K2P Channel in Hippocampal Astrocytes - Woo, Dong Ho; Bae, Jin Young; Nam, Min-Ho; An, Heeyoung; Ju, Yeon Ha; Won, Joungha; Choi, Jae Hyouk; Hwang, Eun Mi; Han, Kyung-Seok; Bae, Yong Chul; Lee, C. Justin (Frontiers in Cellular Neuroscience, 2018)
Recently, μ-opioid receptor (MOR), one of the well-known Gi-protein coupled receptors (Gi-GPCR), was reported to be highly expressed in the hippocampal astrocytes. However, the role of astrocytic MOR has not been investigated. Here we report that activation of astrocytic MOR by DAMGO, a selective MOR agonist, causes a fast glutamate release using sniffer patch technique. We also found that the DAMGO-induced glutamate release was not observed in the astrocytes from MOR-deficient mice and MOR-shRNA-expressed astrocytes. In addition, the glutamate release was significantly reduced by gene silencing of the TREK-1-containing two-pore potassium (K2P) channel, which mediates passive conductance in astrocytes. Our findings were consistent with the previous study demonstrating that activation of Gi-GPCR such as cannabinoid receptor CB1 and adenosine receptor A1 causes a glutamate release through TREK-1-containing K2P channel from hippocampal astrocytes. We also demonstrated that MOR and TREK-1 are significantly co-localized in the hippocampal astrocytes. Furthermore, we found that both MOR and TREK-1-containing K2P channels are localized in the same subcellular compartments, soma and processes, of astrocytes. Our study raises a novel possibility that astrocytic MOR may participate in several physiological and pathological actions of opioids, including analgesia and addiction, through astrocytically released glutamate and its signaling pathway.